Μια φορά με είχε ρωτήσει εμένα τι άνδρες μ'αρέσουν: Συγκρότηση του έμφυλου εαυτού και (ανα)παραγωγή της ετεροκανονικότητας μέσω του λόγου - Χριστουλάκη, Δάφνη-Νικολέτα (Aegean Working Papers in Ethnographic Linguistics, 2017)
This paper aims to explore how articulations of gender and sexuality and dominant ideas about them emerge through language use. A brief overview of the trajectory of sociolinguistic studies on gender and sexuality is followed by the critical analysis of a short conversation among friends. The notions of member categorization devices, indexicality and communities of practice are central to this analysis. Based on the data, it is argued that gender and sexuality can be constructed and negotiated through everyday conversations in multiple ways, at times conforming to dominant norms and at times disregarding them. Power relations seem to influence the communicative practices employed in the ongoing construction of the gendered and sexual self through linguistic interaction, in which the pervasiveness of heteronormativity is unmissable.